It's always possible - Bedi, Kiran (New Delhi, 1998)
Motivation, persistence and perseverance are the distinct traits of determined, dedicated individuals who can make things happen. It's always possible, even when the task is awesome- transforming the mindsets of human beings.
Keywords: Prisons India